Community Empowerment Through Prohibited Fish Management - Riski Susanto; Reni Susanti; Zainal Fadri; Micheal Lambou (INDEV: International Journal of Islamic Community Development, 2023)
This article describes community empowerment through the management of prohibited fish in Jorong Mapun Nagari Sundata, Lubuk Attitude District, Pasaman Regency. The main problem of this thesis is about how to better manage prohibited fish so that they can reap maximum results every time they are harvested in order to empower the Jorong Mapun community both in terms of development and in terms of social. The purpose of this study is to find out how the strategy is to empower the community through the management of prohibited fish in Jorong Mapun Nagari Sundata, Lubuk Attitude District, Pasaman Regency. To find out the supporting factors in empowering the community through the management of prohibited fish in Jorong Mapun Nagari Sundata, Lubuk Attitude District, Pasaman Regency. To find out what obstacles occur in community empowerment through the management of prohibited fish in Jorong Mapun Nagari Sundata, Lubuk Attitude District, Pasaman Regency.